The Role of Youth in The Development of Rural Human Resources, Dolok Masihul District, Serdang Bedagai Regency - Sitorus, Benry; Nasution, Zulkifli; Purwoko, Agus (Journal of Environmental and Development Studies, 2021)
The purpose of this study was to analyze the Community Satisfaction Index (IKM) and the effectiveness on online-based licensing services in the One Stop Integrated Investment and Licensing Service of Sumatera Utara Province. The analytical method used in this study was descriptive quantitative analysis. The results of the study obtained that the Index of Community Satisfaction with online-based licensing services obtained a value of 86.29. Based on KepMenPAN Number: KEP/25/M.PAN/2/2004 on General Guidelines for the Preparation of Community Satisfaction Index of Government Agency Service Units included in the quality of service "A" with the performance of service units "Very Good" because it was at the IKM Conversion Interval Value between 81.26 - 100.00. The effectiveness obtained a value of 86.02% with a very effective category because it was on interpretation of 81-100%.